1977
DOI: 10.1104/pp.60.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Fixation by Lupin Root Nodules

Abstract: In vivo C02 fixation and in vitro phosphoenolpyruvate (PEP) carboxylase levels have been measured in lupin (Lupinus angustifolius L.) root nodules of various ages. Both activities were greater in nodule tissue than in either primary or secondary root tissue, and increased about 3-fold with the onset of N2 fixation. PEP carboxylase activity was predominantly located in the bacteroid-containing zone of mature nodules, but purified bacteroids contained no activity. Partially purified PEP carboxylases from nodules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…The protocol for the in vivo C 0 2 fixation assay for excised roots was modified from that used by Christeller et al (1977) and Maxwell et al (1984). Excised root tissue (350 mg fresh weight) was labeled with 7.4 X 104 Bq of aqueous NaH14C03 (2.1 X 109 Bq mmol-'; ICN Radiochemicals, Irvine, CA) for 20 min at 23OC.…”
Section: C02 Labeling and Extraction Proceduresmentioning
confidence: 99%
“…The protocol for the in vivo C 0 2 fixation assay for excised roots was modified from that used by Christeller et al (1977) and Maxwell et al (1984). Excised root tissue (350 mg fresh weight) was labeled with 7.4 X 104 Bq of aqueous NaH14C03 (2.1 X 109 Bq mmol-'; ICN Radiochemicals, Irvine, CA) for 20 min at 23OC.…”
Section: C02 Labeling and Extraction Proceduresmentioning
confidence: 99%
“…In amide-exporting legumes, this route via PEPc is vital to provide C skeletons for the assimilation of NH 4 + (Christeller et al ., 1977;Vance et al ., 1985;Vance & Snapp, 1986). Furthermore, PEPc provides a portion of the C for both malate and aspartate synthesis (Romanov et al ., 1985).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in nodules of amide-exporting plants like lupin (3). Davies (7) has suggested that PEP carboxylase may function in duo with malate dehydrogenase as a pH stat for regulating intracellular pH.…”
mentioning
confidence: 99%
“…Roots and nodules of N2-fixing leguminous plants such as lupins (3,16), peas (19,20), broad beans (15), garden beans (5), cowpeas (16), and soybeans (4) possess an active system for assimilating CO2. Although lesser activities of other carboxylating activities have been reported (8,15), PEP' carboxylase appears to be the primary enzyme responsible for CO2 fixation in these tissues (22).…”
mentioning
confidence: 99%